2019
DOI: 10.1002/hpm.2872
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous care for patients with type 2 diabetes using mobile health application: A randomised controlled trial

Abstract: Summary Background Type 2 diabetes is a worldwide disorder that affects millions of people and can exert negative clinical and social effects on the patients. In some previous studies, mobile health applications have been used as a means of clinical intervention. However, the therapeutic effect of continuous care through mobile phone applications for patients with type 2 diabetes remains unclear. Objective This study aimed to explore the clinical effect of continuous care for patients with type 2 diabetes usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 29 publications
0
43
0
4
Order By: Relevance
“…The chronic disease most commonly addressed was diabetes ( n = 29, 42.0%), with 16 studies sampling type 2 diabetes (T2DM) population in 19 articles 30 33 , 42 , 48 , 49 , 52 63 , 10 focusing on type 1 diabetes (T1DM) 51 , 64 72 and three enrolling both T1DM and T2DM patients in four articles 45 , 73 75 . Thirteen studies (18.8%) targeted cardiovascular diseases, with five focusing on heart failure 35 , 36 , 76 – 78 and the remaining on cardiovascular diseases (CVDs) 34 , 38 , 39 , 79 84 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chronic disease most commonly addressed was diabetes ( n = 29, 42.0%), with 16 studies sampling type 2 diabetes (T2DM) population in 19 articles 30 33 , 42 , 48 , 49 , 52 63 , 10 focusing on type 1 diabetes (T1DM) 51 , 64 72 and three enrolling both T1DM and T2DM patients in four articles 45 , 73 75 . Thirteen studies (18.8%) targeted cardiovascular diseases, with five focusing on heart failure 35 , 36 , 76 – 78 and the remaining on cardiovascular diseases (CVDs) 34 , 38 , 39 , 79 84 .…”
Section: Resultsmentioning
confidence: 99%
“…The final 20 studies included both HCP involvement and higher-intensity technology automation. Some of the app interventions calculated and suggested optimal insulin doses under general professional oversight and with facilitated patient–physician communication 51 , 56 , 64 , 66 , while the remaining provided automatic machine-based feedbacks as a first-level support with the possibility for professionals to intervene if warranted 30 , 31 , 34 , 49 , 50 , 52 , 57 , 60 , 76 , 77 , 86 , 88 , 89 , 91 , 98 , 102 .…”
Section: Resultsmentioning
confidence: 99%
“…Teach-back communication as an intervention/exposure strategy was utilized in 6 studies out of which 3 were RCTs, 2 were CS and 1 study was a cross-sectional study (miscellaneous). Among the studies utilizing mHealth ( n = 11), 7 studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ] showed significant reduction ( p < 0.05) in hospital readmissions while four studies [ 33 , 34 , 35 , 36 ] did not show any significant reduction ( p > 0.05) in readmissions. Among the teach-back communication group ( n = 6), the majority of the studies ( n = 5) [ 37 , 38 , 39 , 40 , 41 ] showed a significant reduction in hospital readmissions while one publication [ 42 ] did not show any significant hospital readmission reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Menurunkan kadar hbA1c, profil lipid, dan memperbaiki level efikasi diri serta level insulin pasien diabetes melitus tipe 2 (Wang, et al, 2019) (15) RCT 120 responden dengan usia 30-60 tahun 6 bulan…”
Section: Bulanunclassified